Concentration- and time-dependence of phosphorylation events stimulated by fibroblast growth factor-4 (FGF-4) in Rama 27 fibroblasts - Alsadun, Marim M.; Su, Dunhao; Yates, Edwin A.; Fernig, David G. (bioRxiv, 2025)
Gradients of FGFs are an essential feature of many developmental processes. Thus, FGF2 stimulates different responses at high and low concentrations, while FGF4 gradients are critical, e.g., in limb development., but it is not known if responses to FGF4 differ in a concentration-dependent manner. Employing rat mammary (Rama) 27 fibroblasts, we therefore measured the FGF4 concentration- and time-dependence of the simulation of phosphorylation of FRS2α, MAPK1 and MAPK3 which are downstream of the FGF receptor (FGFR1c). At 10 pg/mL FGF4 caused a very weak phosphorylation of FRS2α at Y435 and Y196 and a stronger one of MAPK1 and MAPK3 that oscillated with maximum levels after 30 min and 240 min stimulation. The phosphorylation of these proteins at 1 ng/mL FGF4 was considerably stronger and showed a similar oscillation. At 10 ng/mL FGF4, the phosphorylation of FRS2α reached an early peak after 5 min, declined at 15 min and then rose again at 30 min before declining to the end of the time-course at 240 min, whereas the phosphorylation of MAPK1 and MAPK3 was strong after 5 minutes, reached a maximum after 30 minutes and then declined gradually. At 1 µg/mL and 3 µg/mL FGF4 after 15 min and 60 min the phosphorylation of FRS2α, MAPK1 and MAPK3 was much lower at 60 min compared to that observed at lower concentrations of FGF4. The data indicate that at low concentrations FGF4 elicits an oscillatory response at the level of phosphorylation of FRS2α and of MAPK1 and MAPK3, whereas a bell-shaped dose response may occur at the highest concentrations of FGF4. The addition of exogenous heparin, an effective mimic of endogenous heparan sulfate, suggests that there may be an influence of the interaction of FGF4 with pericellular matrix and the dose-and time-dependence of the phosphorylation of FRS2α and MAPK1and MAPK3.